360=x(x-3)+(x+8)+(x-3)

Simple and best practice solution for 360=x(x-3)+(x+8)+(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 360=x(x-3)+(x+8)+(x-3) equation:



360=x(x-3)+(x+8)+(x-3)
We move all terms to the left:
360-(x(x-3)+(x+8)+(x-3))=0
We calculate terms in parentheses: -(x(x-3)+(x+8)+(x-3)), so:
x(x-3)+(x+8)+(x-3)
We multiply parentheses
x^2-3x+(x+8)+(x-3)
We get rid of parentheses
x^2-3x+x+x+8-3
We add all the numbers together, and all the variables
x^2-1x+5
Back to the equation:
-(x^2-1x+5)
We get rid of parentheses
-x^2+1x-5+360=0
We add all the numbers together, and all the variables
-1x^2+x+355=0
a = -1; b = 1; c = +355;
Δ = b2-4ac
Δ = 12-4·(-1)·355
Δ = 1421
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{1421}=\sqrt{49*29}=\sqrt{49}*\sqrt{29}=7\sqrt{29}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(1)-7\sqrt{29}}{2*-1}=\frac{-1-7\sqrt{29}}{-2} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(1)+7\sqrt{29}}{2*-1}=\frac{-1+7\sqrt{29}}{-2} $

See similar equations:

| x-5-8=-1 | | -(6h+7)+8=-29 | | 50x=40(x+10) | | -216=6(4n-8) | | 110=y-16 | | -216=6(4n-8 | | 11/8x=91 | | 3/2y-3=-2/3y-1/6 | | |18d-4d|+5=13 | | 0.5x-5+0.66x=1.17x+4 | | -5x7=27 | | 0.15x=x-0.6x-6,00,000 | | 3x-12+×+36=90 | | 3/5n+9/10=-n/5-23/10 | | -1=8+8x | | -5(x)7=27 | | x+16.51=9.51 | | 2-15n=-5(-3n+2) | | x-9.51=16.52 | | 4x-5x+9=5-9 | | x+9.51=16.51 | | -33+y=18 | | x-16.51=9.51 | | 3.8x-0.1=22.7 | | 8(-5b+1)+b=125 | | 7(y+4)+y=4(y+2)-4 | | -20+f=-45 | | -10+4n=-46 | | 5k+-3k=14 | | 27x2+39x−10=0 | | -13.21−20t=15.31−16.9t | | 2(x+5(6x-1)=120 |

Equations solver categories